Teja – eco indikator / Azizul Mohd Hasan - Mohd Hasan, Azizul (Universiti Teknologi MARA, Kedah, 2019)
TEJA - Eco Indicator created from a ‘Clitoriaternatea’ species flower. It is a bean type plant that grows creeping and has blue flower. It is a herb plant that grows in Khatulistiwa or Tropical Monsun weathered countries. ‘Clitoriaternatea’ produces blue solution when soaked in water. It is caused by blue pigment called ‘Anthocyanin’ that makes the flower blue. It is tasteless, odourless, water soluble and it changes colour when mixed with acid or alkaline, depends on pH value and strong level of the solution. In neutral state, the ‘Anthocyanin’ stays blue. It changes to pink or purple in acidic solution and to green or yellow in alkaline. It turns to crystal clear if the solution is too alkaline as the ‘Anthocyanin’ is totally bleached. This element allows ‘Clitoriaternatea’ as an indicator to detect acid or alkaline for any solutions from local resource.